2021
DOI: 10.3390/plants11010082
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals and Biological Activities of Barleria (Acanthaceae)

Abstract: Plant species belonging to the family Acanthaceae are globally known to possess various medicinal properties and have cultural and economic importance in both traditional medicine and horticulture. They are important to both animals and humans and are used as food or for ornamental purposes worldwide. Barleria is the third largest genus in the family Acanthaceae. A few of the highly important and reported species of Barleria include B. prionitis, B. cristata, B. grandiflora, and B. lupulina. The flowers, leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 212 publications
(190 reference statements)
0
20
0
Order By: Relevance
“…Many of the detected compound such as shanzhiside methylester and barlerin showed a similar isotopic abundance, which helped us in further identification. Iridoid glycosides and phenolic compounds have been reported from aerial parts of Barleria species (Gangaram et al, 2022), however as shown in our study, they are distributed in all parts of the plant, including leaf, root, stem and flower (Figure 2). The study also helped us to analyse the distribution pattern and abundance of these compounds in both the plants.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Many of the detected compound such as shanzhiside methylester and barlerin showed a similar isotopic abundance, which helped us in further identification. Iridoid glycosides and phenolic compounds have been reported from aerial parts of Barleria species (Gangaram et al, 2022), however as shown in our study, they are distributed in all parts of the plant, including leaf, root, stem and flower (Figure 2). The study also helped us to analyse the distribution pattern and abundance of these compounds in both the plants.…”
Section: Discussionmentioning
confidence: 51%
“…It is found in India and also distributed in different parts of Asia and Africa ( Chen et al., 1998 ). Aerial parts of this plant has long been used in the treatment of diseases such as, toothache, whooping cough, respiratory and gastrointestinal disorders, fever, swelling, artheritis, skin disorders, jaundice etc ( Amoo et al., 2009 ; Gangaram et al., 2022 ). Extracts collected from aerial parts of the plant have shown to possess antioxidant, antibacterial, antiviral, anti-inflammatory, hepatoprotective, antidiabetic, antifertility, immune modulating activity and acetylcholinesterase inhibitory activities ( Chen et al., 1998 ; Gupta et al., 2000 ; Singh et al., 2003 ; Singh et al., 2005 ; Verma et al., 2005 ; Kosmulalage et al., 2007 ; Amoo et al., 2009 ; Dheer and Bhatnagar, 2010 ; Chavan et al., 2014 ; Sharma et al., 2014 ; Gangaram et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the five Barleria cp genomes compared to B. prionitis was performed and was found to be 152,217 bp in length [ 23 ]. The identification of various Barleria species should be performed in order to use the correct species for the right purpose, corresponding to the bioactive compounds contained and their properties in natural product creation for humans, such as medicine, cosmetics, and nutraceutical supplements [ 1 , 3 , 4 , 5 , 6 , 7 ]. Several species of Barleria are known for their medicinal or ornamental values [ 6 , 43 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The two sequences divided each species of Barleria , but it was noted that A. paniculata was inserted in the in-group of the Barleria species. Presently, no one has comprehensively reported on the species within Barleria using the existing literature in a clear and concise manner [ 7 ]. Therefore, the cp genome variations of each studied Barleria species have been used as an accurate marker for species authentication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation